Prevalence of malnutrition in patients with acute coronary syndrome undergoing coronary angiography in Thailand: A retrospective observational study - Wattanasiriporn, Wittawat; Sunawin, Methat; Arayangkoon, Chantisa (Narra Sains Indonesia, 2026)
Malnutrition is an important prognostic factor in patients with acute coronary syndrome (ACS), but it remains under-recognized in routine practice, particularly in Thailand, where local data are limited, and no population-specific nutritional screening tool has been validated. The Prognostic Nutritional Index (PNI) and Nutritional Risk Index (NRI) have been associated with mortality and major adverse cardiovascular events (MACEs) in patients with ACS, but their clinical usefulness in Thai patients remains unclear. This study aimed to determine the prevalence of malnutrition among patients with ACS undergoing coronary angiography (CAG) at Rajavithi Hospital, Bangkok, Thailand, and to assess the clinical usefulness of PNI and NRI in this setting. The secondary objective was to evaluate 1-year all-cause mortality and the occurrence of MACEs according to nutritional status. This study included 244 adult patients with ACS who were admitted between January 2023 and December 2024, underwent CAG, and completed a 1-year follow-up. Nutritional status was assessed using PNI and NRI, and categorized as severe, moderate, or no malnutrition. The primary outcome was 1-year all-cause mortality, while the secondary outcome was MACEs, defined as a composite of cardiovascular death, non-fatal myocardial infarction, non-fatal ischemic stroke, hospitalization for heart failure, and hospitalization for unstable angina. Associations between nutritional status and outcomes were examined using logistic regression. According to PNI, 43.8% of patients were malnourished, including 27.0% with severe malnutrition and 16.8% with moderate malnutrition. In contrast, NRI classified 99.6% of patients as severely malnourished. The 1-year all-cause mortality rate was 28.3%, and the MACE rate was 28.7%. Based on PNI, severe and moderate malnutrition were associated with higher mortality than no malnutrition (62.1% and 31.7% vs 10.9%, respectively). Severe malnutrition was associated with 13.34-fold higher odds of death (odds ratio (OR) 13.34; 95%CI: 6.41–27.71), while moderate malnutrition was associated with 3.78-fold higher odds (OR 3.78; 95%CI: 1.61–8.82). Severe and moderate malnutrition were also associated with higher odds of MACEs (OR 2.65; 95%CI: 1.38–5.06 and OR 2.89; 95%CI: 1.36–6.11, respectively). Malnutrition was common among Thai patients with ACS undergoing CAG and was strongly associated with adverse 1-year outcomes. Compared with NRI, PNI provided more clinically meaningful stratification in this cohort. Although formal comparative performance analyses were not performed, PNI may be a practical tool for nutritional risk assessment in routine ACS care.